Environment‐adaptive coassembly/self‐sorting and stimulus‐responsiveness transfer based on cholesterol building blocks - Xing, Pengyao (2018)
Manipulating the property transfer in nanosystems is a challenging task since it requires switchable molecular packing such as separate aggregation (self‐sorting) or synergistic aggregation (coassembly). Herein, a unique manipulation of self‐sorting/coassembly aggregation and the observation of switchable stimulus‐responsiveness transfer in a two component self‐assembly system are reported. Two building blocks bearing the same cholesterol group give versatile topological structures in polar and nonpolar solvents. One building block (cholesterol conjugated cynanostilbene, CCS) consists of cholesterol conjugated with a cynanostilbene unit, and the other one (C10CN) is comprised of cholesterol connected with a naphthalimide group having a flexible long alkyl chain. Their assemblies including gel, crystalline plates, and vesicles are obtained. In gel and crystalline plate phases, the self‐sorting behavior dominates, while synergistic coassembly occurs in vesicle phase. Since CCS having the cyanostilbene group can respond to the light irradiation, it undergoes light‐induced chiral amplification. C10CN is thermally responsive, whereby its supramolecular chirality is inversed upon heating. In coassembled vesicles, it is interestingly observed that their responsiveness can be transferred by each other, i.e., the C10CN segment is sensitive to the light irradiation, while CCS is thermoresponsive. This unprecedented behavior of the property transfer may shine a light to the precise fabrication of smart materials.